Neoadjuvant chemotherapy plus camrelizumab for locally advanced cervical cancer (NACI study): a multicentre, single-arm, phase 2 trial - Li, Kezhen; Chen, Jing; Hu, Yingjie; Wang, Yan-Zhou; Shen, Yuanming; Chen, Gang; Peng, Wenju; Fang, Zixuan; Xia, Bairong; Chen, Xiaojun; Song, Kun; Wang, Yingmei; et al. (The lancet oncology, 2024)
Locally advanced cervical cancer constitutes around 37% of cervical cancer cases globally and has a poor prognosis due to limited therapeutic options. Immune checkpoint inhibitors in the neoadjuvant setting could address these challenges. We aimed to investigate the efficacy and safety of neoadjuvant chemo-immunotherapy for locally advanced cervical cancer. In this single-arm, phase 2 trial, which was done across eight tertiary hospitals in China, we enrolled patients aged 18–70 years with untreated cervical cancer (IB3, IIA2, or IIB/IIIC1r with a tumour diameter ≥4 cm [International Federation of Gynecology and Obstetrics, 2018]) and an Eastern Cooperative Oncology Group performance status of 0 or 1. Eligible patients underwent one cycle of priming doublet chemotherapy (75–80 mg/m2 cisplatin, intravenously, plus 260 mg/m2 nab-paclitaxel, intravenously), followed by two cycles of a combination of chemotherapy (cisplatin plus nab-paclitaxel) on day 1 with camrelizumab (200 mg, intravenously) on day 2, with a 3-week interval between treatment cycles. Patients with stable disease or progressive disease received concurrent chemoradiotherapy, and patients with a complete response or partial response proceeded to radical surgery. The primary endpoint was the objective response rate, by independent central reviewer according to Response Evaluation Criteria in Solid Tumours, version 1.1. Activity and safety were analysed in patients who received at least one dose of camrelizumab. This study is registered with ClinicalTrials.gov, NCT04516616, and is ongoing. Between Dec 1, 2020, and Feb 10, 2023, 85 patients were enrolled and all received at least one dose of camrelizumab. Median age was 51 years (IQR 46–57) and no data on race or ethnicity were collected. At data cutoff (April 30, 2023), median follow-up was 11·0 months (IQR 6·0–14·5). An objective response was noted in 83 (98% [95% CI 92–100]) patients, including 16 (19%) patients who had a complete response and 67 (79%) who had a partial response. The most common grade 3–4 treatment-related adverse events during neoadjuvant chemo-immunotherapy were lymphopenia (21 [25%] of 85), neutropenia (ten [12%]), and leukopenia (seven [8%]). No serious adverse events or treatment-related deaths occurred. Neoadjuvant chemo-immunotherapy showed promising antitumour activity and a manageable adverse event profile in patients with locally advanced cervical cancer. The combination of neoadjuvant chemo-immunotherapy with radical surgery holds potential as a novel therapeutic approach for locally advanced cervical cancer. National Key Technology Research and Development Program of China and the National Clinical Research Center of Obstetrics and Gynecology.